2014
DOI: 10.1097/ncc.0b013e318289a6e2
|View full text |Cite
|
Sign up to set email alerts
|

Stressors, Stress Response, and Cancer Recurrence

Abstract: Although at present, there is no evidence indicating a causal relationship between stress and cancer recurrence, attending to the reduction in a cancer survivor's stress response can improve emotional well-being and quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…One of the things that I did after my initial shock wore off was announce it on (Rodriguez & Kelly, 2006;Slepian, Masicampo, & Ambady, 2014). This is especially pertinent to individuals diagnosed with IBD, as stress is shown to cause adverse outcomes in these individuals (Cámara, Ziegler, Begré, Schoepfer, & von Känel, 2009); meanwhile, the role of stress and cancer recurrence remains unclear (Todd, Moskowitz, Ottati, & Feuerstein, 2014). Shannon, 37 (had an ostomy since she was 1 month old due to being born with cloacal exstrophy), explained that sharing with those close to her helped her were judging me, at that point, they just wanted to know more, and that was a good feeling for me.…”
Section: Connecting To Others With An Ostomy Many Participants Activmentioning
confidence: 99%
“…One of the things that I did after my initial shock wore off was announce it on (Rodriguez & Kelly, 2006;Slepian, Masicampo, & Ambady, 2014). This is especially pertinent to individuals diagnosed with IBD, as stress is shown to cause adverse outcomes in these individuals (Cámara, Ziegler, Begré, Schoepfer, & von Känel, 2009); meanwhile, the role of stress and cancer recurrence remains unclear (Todd, Moskowitz, Ottati, & Feuerstein, 2014). Shannon, 37 (had an ostomy since she was 1 month old due to being born with cloacal exstrophy), explained that sharing with those close to her helped her were judging me, at that point, they just wanted to know more, and that was a good feeling for me.…”
Section: Connecting To Others With An Ostomy Many Participants Activmentioning
confidence: 99%
“…10,11 Similarly, studies on colorectal cancers have mostly demonstrated a protective effect. 24 However, other researchers claim that psychological stress cannot be considered a direct cancer risk factor [25][26][27] and thus posit that stress impacts the risk of cancer through secondary mechanisms. 19,20 Stress works through the sympathetic nervous system and hypothalamic-pituitary-adrenal axis activation, together with related hormones that have an impact on the tumor microenvironment.…”
Section: Introductionmentioning
confidence: 99%
“…23 Studies in humans have indicated that changes in DNA methylation can be long-lasting consequences of stressor exposure. 24 However, other researchers claim that psychological stress cannot be considered a direct cancer risk factor [25][26][27] and thus posit that stress impacts the risk of cancer through secondary mechanisms. These may include behaviors such as smoking, insomnia, alcohol abuse, and poor hygienic conditions, which might interact with psychological responses to stressors.…”
Section: Introductionmentioning
confidence: 99%
“…Many patients are anxious about cancer recurrence, the uncertainty of death, and the side effects of cancer treatment, which lower their QoL. [2345] On the other hand, 44.6% of cancer patients use CAM. Most patients use natural products, such as vitamins, minerals, traditional Chinese medicine, and probiotics.…”
Section: Introductionmentioning
confidence: 99%